White pages: Israeli censorship of Palestinian textbooks in East Jerusalem. Issue 4 (8th August 2018) - Alayan, Samira
ABSTRACT: This study examined History textbooks taught in East Jerusalem. The political context of East Jerusalem and its education system manifests a continuous power struggle between the Palestinian National Authority and Israeli authorities, in this case, the Israeli Ministry of Education. Through analyzing the textbooks, this study speaks of the power dynamics and systems of political control manifested through the Israeli censorship. The aim of this paper is to present the intricate power relations of the education system in East Jerusalem as it is revealed in the censorship of textbooks. In analyzing the content censored in textbooks for elementary and high schools, three main censorship categories emerged: "erasing symbols, " "leaving out segments, " and "deleting the content of whole pages." These are presented and analyzed within a political context in the study.